Housing-related companion animal relinquishment across 21 animal shelters in the United States from 2019–2023 - Applebaum, Jennifer W.; Loney, Lauren; Horecka, Kevin; Graham, Taryn M. (Frontiers in Veterinary Science, 2024)
Housing issues are a major contributor to companion animal relinquishment in the United States and beyond. In this study, we analyze a database of shelter intake records from 2019–2023 from 21 shelters across the United States to assess rates and subtypes of housing relinquishment, characteristics and outcomes of the relinquished animals, and longitudinal trends in housing relinquishment. Housing issues represented 14% (n = 28,424) of overall intakes in the broader database (N = 1,021,204 total intake records). Housing relinquishment subtypes were unspecified (54%), pet-related restrictions (27%), landlord issues (8%), housing loss (5%), and unhoused owners (5%). Large (mean weight: 55 lbs) and small dogs (mean weight: 11 lbs) were most common. Pit bull-type dogs comprised 12% of the overall relinquishments and mixed-breed dogs were 35%. Most animals had a live outcome, but live outcomes decreased over time (p < 0.001, z = −6.91, slope = −0.11), and pit bull-type dogs (X2(1) = 243.63, p < 0.001) and animals relinquished by unhoused owners (OR = 0.64, p < 0.05) were most at risk of euthanasia or other shelter death. Over the study period, intakes due to loss of home increased (p < 0.001, z = 9.82, slope = 0.29), while intakes due to pet restrictions (p < 0.001, z = −6.82, slope = −0.17) and landlord issues decreased (p < 0.001, z = −4.89, slope = −0.08). Overall cat intakes increased (p < 0.001, z = 3.60, slope = 7.34), while dog intakes decreased (p < 0.001, z = −4.89, slope = −0.08). The number of intakes that were pit bull-type dogs (compared to all other breeds) decreased over time (p < 0.001, z = −4.56, slope = −0.06), as did average animal weight (p < 0.001, z = −4.42, slope = −0.07) and age (p < 0.001, z = −7.88, slope = −0.16). We discuss these findings in the context of the previous shelter and pet-friendly housing research and broader housing trends and policies in the United States.